Death Due to Decapitation in Two Motorcyclists: A Description of a Unique Case and a Brief Review of the Literature1. Issue 3 (16th December 2016) - Osculati, Antonio; Visonà, Silvia D.; Della Chiesa, Laura; Navarra, Filippo; Calbi, Andrea; Andrello, Luisa
Abstract: Deaths due to decapitation, especially related to traffic accidents, are rarely found in forensic practice. The present case involves a man and a woman who died from decapitation due to an unusual mechanism while they were riding on a motorbike down a mountain road. The autopsy, which was completed as a physics study, allowed the accident to be reconstructed as follows: A plastic cable that had detached from a timber‐transporting machine whipped the road and hit the two motorcyclists. The impact resulted in the complete severing of both riders' heads. Involving different scientists in this accident investigation was crucial to understanding the dynamics of the accident. In fact, in addition to scene inspection and autopsy, a physics study was carried out on the cable and the clamp involved, which led to an explanation for the abrupt movement of the cable and, thus, to a thorough reconstruction of the accident.